JAVANESE FAMILY ETHIC IN SERAT SALOKATAMA - Mustolehudin, Mustolehudin; Muawanah, Siti; Rahmah, Yulinar Aini; Mibtadin, Mibtadin; Sulaiman, Sulaiman (Analisa: Journal of Social Science and Religion, 2022)
The role of family has significant in maintaining harmonious life for each family member. For playing the family role, it is possible for the family refers to an ethical value. Javanese people maintain highly respectable values from their ancestors transferred by poets in the past. One of them was Mangkunegara IV, a descendant of King Surakarta who was prolific in producing some forms of literary works, such as serat piwulang. This article is a discussion about Serat Salokatama, one of Mangkunegara IV’s valuable works. By using literature study and hermeneutical approaches, this study found out some important findings related to Javanese ethic. First, the Serat Salokatama is a work which contains some values important for family life. The most important is religious value as it will produce other respectable values, such as honesty, vigilant, patient, politeness, and kindness, humble, toughness and never giving up easily, and not arrogant. Second, the Serat Salokatama also teaches its readers the significance of interactive and constructive dialogue to maintain good family lives.